2015
DOI: 10.1159/000381190
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effects of Fenofibrate via Modulation of LKB1/AMPK mRNA Expression and Endothelial Dysfunction in a Rat Model of Diabetic Nephropathy

Abstract: This study was conducted to investigate whether the renoprotective effects of fenofibrate are mediated via attenuation of endothelial dysfunction and modulating the mRNA expression of adenosine monophosphate-activated protein kinase (AMPK) and its downstream kinase liver kinase B1 (LKB1) in rats with diabetic nephropathy (DN).Diabetes was induced by a single intraperitoneal injection of streptozotocin (55 mg kg-1). Fenofibrate (100 mg kg-1, p.o.) was given to diabetic rats daily for 12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 49 publications
2
15
0
1
Order By: Relevance
“…AMPK activation promotes mitochondrial substrate utilisation and ATP generation, in parallel with stimulation of antioxidant gene expression to ensure an optimal redox balance [123]. In diabetes, AMPK is downregulated in the kidney and associated with impaired mitochondrial function [124] and reduced AMPK-mediated inhibition of NADPH oxidase (Nox2) resulting in increased oxidant species production [85,125]; upregulation/activation of AMPK has been proposed as a potential therapeutic intervention in the diabetic kidney [126].…”
Section: Oxidative Stress In the Glomerulusmentioning
confidence: 99%
“…AMPK activation promotes mitochondrial substrate utilisation and ATP generation, in parallel with stimulation of antioxidant gene expression to ensure an optimal redox balance [123]. In diabetes, AMPK is downregulated in the kidney and associated with impaired mitochondrial function [124] and reduced AMPK-mediated inhibition of NADPH oxidase (Nox2) resulting in increased oxidant species production [85,125]; upregulation/activation of AMPK has been proposed as a potential therapeutic intervention in the diabetic kidney [126].…”
Section: Oxidative Stress In the Glomerulusmentioning
confidence: 99%
“…Reduced AMPK, as seen in the diabetic kidney of both rodents and humans [65], is associated with reduced catabolic activity (mitochondrial function) [65], and reduced AMPK-mediated inhibition of NADPH oxidase (Nox2) resulting in increased ROS production [71,72]. Taken together, these results suggest that, in the diabetic kidney, upregulation of AMPK could be therapeutically beneficial in DN [73] to regulate nutrient utilisation and mitochondrial function towards maintenance of an optimum redox balance.…”
Section: Reactive Oxygen Species and Diabetic Nephropathymentioning
confidence: 99%
“…Because partial renal protection by FF ( Figures 5C, 6) remained in Akt2-KO mice, we further showed that FF also stimulates AMP-activated protein kinase (AMPK)-mediated renal protection in T1D-associated DN (Figures 7). In addition, although we showed that AMPKα was activated using a phospho-specific antibody, but we were unable to conclude that FF-activated renal protection was AMPKα-dependent because we did not examine other AMPK isoforms, although in previous reports describing FF activation of AMPK [25][26][27] , only couple of them directly or indirectly measured AMPKα induction by FF and hardly any mentioned AMPK isoforms [25][26][27] .…”
Section: Discussionmentioning
confidence: 77%
“…In the current study (Figure 8), we propose that AMPK is partially responsible for the FGF21-mediated renal protection from HG because the use of an AMPK inhibitor alongside Akt2-siRNA silencing abolished the preventive effect of FF on the HG-induced phenotype of HK-2 cells. In fact, Al-Rasheed et al have previously described the involvement of the activation of liver kinase B1/AMPK in the FF-induced protection against DN in T1D rats [27] . Although we and others have not determined how FGF21 activates AMPK in T1D mice and rats [27] , there is convincing evidence that FGF21 activates the AMPK pathway, either directly through fibroblast growth factor receptor 1/β-klotho signaling, or indirectly by stimulating the secretion of adiponectin and corticosteroids, which can activate AMPK signaling in their target tissues [43] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation